The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00296-016-3515-2
|View full text |Cite
|
Sign up to set email alerts
|

Abducens nerve palsy in a girl with incomplete Kawasaki disease

Abstract: Kawasaki disease (KD) is a systemic vasculitis that can involve the nervous system, including the cranial nerves. Central nervous system findings, especially irritability, lethargy, and aseptic meningitis, occur in 1-30 % of KD patients (1). Cranial nerve palsies are seen rarely, and abducens nerve palsy has been reported in only three children. We describe a 2.5-year-old girl with incomplete KD who developed transient abducens nerve palsy after intravenous immunoglobulin (IVIG) treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The patient recovered completely after 2 weeks, and aseptic meningitis was considered the underlying cause. Furthermore, two case reports described patients with Kawasaki disease who developed abducens nerve palsy after IVIG therapy ( 74 , 75 ). However, whether abducens nerve palsy was directly related to immunoglobulin therapy in these cases is unclear.…”
Section: Classification Of Adverse Effectsmentioning
confidence: 99%
“…The patient recovered completely after 2 weeks, and aseptic meningitis was considered the underlying cause. Furthermore, two case reports described patients with Kawasaki disease who developed abducens nerve palsy after IVIG therapy ( 74 , 75 ). However, whether abducens nerve palsy was directly related to immunoglobulin therapy in these cases is unclear.…”
Section: Classification Of Adverse Effectsmentioning
confidence: 99%
“…tic meningitis, cranial nerve palsy, 15 and prolonged partial seizures with bilateral subdural collections. 16 Endothelial cell dysfunction in KD patients may not be restricted to coronary vessels, and previous studies have suggested that both migraines and Raynaud's phenomenon may be consequences of KD.…”
mentioning
confidence: 99%
“…Due to the low number of case reports, we could not safely conclude that abducens nerve palsy was associated with greater disease severity. [54][55][56][57] Sensorineural hearing loss has also been reported in children with Kawasaki disease and usually appears in the first days of the disease. 58 The mechanism of this complication is not clear, but it could be the result of aseptic inflammation of the vestibulocochlear nerve.…”
Section: Other Cranial Nervesmentioning
confidence: 97%
“…In general, most authors agree that neurological complications in Kawasaki disease reflect an increased underlying inflammatory burden. 10,13 15 Ishida et al, 26 Sabatier et al, 16 Yamazaki-Nakashimada et al, 25 Wang et al, 17 Ahn et al, 24 Tanaka et al, 28 Wada et al, 22 Du et al, 27 Suda et al, 18 Hoshino et al, 29 Fujiwara et al, 19 Laxer et al, 20 51 Stowe, 50 Khubchandani and Dhanrajani, 49 Kocabas et al, 48 Thapa, 47 Kaur et al, 46 Lim et al, 45 Li et al, 43 Wright et al, 44 Larralde et al, 42 Poon et al 52 Abducens nerve palsy 4 (case reports) Emiroglu et al, 54 Rodriguez-Lozano et al, 55 Guven et al, 56 Wurzburger et al 57 Articles identified by our literature search consisted mostly of case reports or case series. Prospective and retrospective studies are uncommon and can be attributed to the relative rarity of neurological complications in this entity.…”
Section: Neurological Manifestationsmentioning
confidence: 99%